Revolutionizing economic and democratic systems : reinventing the third way - Nordberg, Kenneth, 1980- (Palgrave Macmillan, 2017)
This book responds to an increasingly pluricentric, reflexive, and flexible society as a result of globalization and economic liberation from the bureaucratic-political system. The third industrial revolution saw citizens, companies, and the economy acting in functional networks rather than in static ones, making top-down governing ever more difficult. Despite this, society systems created in the wake of the second industrial revolution linger on and must adapt to the globalized, digitized reality in order to stay necessary and relevant. Through a theoretical discussion and four empirical cases studying governance and innovation systems, this volume is the first to describe the causes behind the impasse Western society seems to find itself in and suggests inclusive economic and democratic structures working in a bottom-up fashion as a way out. By understanding local circumstances as well as the innovative power of inclusive and participative structures, we can begin to pave the way to legitimate governance and growth. This book adds to the academic literature on democracy, governance, economy, and innovation systems for researchers and scholars of political science, social science, and economics.
Keywords: Mixed economy.; Economics.; elektronické knihy; electronic books